2021
DOI: 10.1093/advances/nmab001
|View full text |Cite
|
Sign up to set email alerts
|

Total, Dietary, and Supplemental Magnesium Intakes and Risk of All-Cause, Cardiovascular, and Cancer Mortality: A Systematic Review and Dose–Response Meta-Analysis of Prospective Cohort Studies

Abstract: A meta-analysis of prospective studies was conducted to examine the association of total, supplemental, and dietary magnesium intakes with risk of all-cause, cancer, and cardiovascular disease (CVD) mortality and identify the dose–response relations involved in these association. We performed a systematic search of PubMed, Scopus, Google Scholar, and ISI Web of Knowledge up to April 2020. Prospective cohort studies that reported risk estimates for the association between total, supplemental, and dietary magnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 62 publications
0
19
0
1
Order By: Relevance
“…Previous studies have investigated the association between individual antioxidant micronutrients and mortality, but with inconsistent conclusions. Some studies reported an inverse association between intakes of vitamins A, C, E, zinc, selenium, and magnesium and the risk of mortality ( 13 , 14 , 34 , 35 ), whereas others found no significant association ( 12 , 36 , 37 ). For instance, Enstrom et al found that the higher vitamin C intake was inversely associated with death from all-cause and CVD in the NHANES I Epidemiologic Follow-up Study (NHEFS) among 11,348 US adults ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the association between individual antioxidant micronutrients and mortality, but with inconsistent conclusions. Some studies reported an inverse association between intakes of vitamins A, C, E, zinc, selenium, and magnesium and the risk of mortality ( 13 , 14 , 34 , 35 ), whereas others found no significant association ( 12 , 36 , 37 ). For instance, Enstrom et al found that the higher vitamin C intake was inversely associated with death from all-cause and CVD in the NHANES I Epidemiologic Follow-up Study (NHEFS) among 11,348 US adults ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of prospective studies (including over 1 million participants) was conducted to examine the association of total, supplemental, and dietary Mg intakes with the risk of CVD mortality risk, and showed no association with a lower CVD mortality risk. The study, however, showed that consumption of Mg from dietary sources may be beneficial in reducing allcause and cancer mortality [67]. The role of dietary Mg intake in reducing CVD mortality has been described with a dose-response relationship irrespective of gender [68] and only found among women [69].…”
Section: Magnesium and Cardiovascular Functionmentioning
confidence: 98%
“…Almonds are a rich source of magnesium, whose consumption from dietary sources has been shown to be beneficial in reducing cancer mortality [ 112 ]. Furthermore, a recent systematic review comprehensive of 49 clinical trials reported a beneficial effect of oral prescribed magnesium therapy against hypertension [ 113 ].…”
Section: Nuts and Healthmentioning
confidence: 99%